2016
DOI: 10.18553/jmcp.2016.22.9.1088
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Tofacitinib Treatment in Rheumatoid Arthritis: Modeling the Cost of Treatment Strategies in the United States

Abstract: This study was funded by Pfizer, which determined the research topic and paid York Health Economics Consortium to develop the analysis and conduct the research. York Health Economics Consortium has received consultancy fees from Pfizer. Gerber, Wallenstein, Mendelsohn, Bourret, Singh, and Moynagh are employees and shareholders of Pfizer. Editorial support was funded by Pfizer and was provided by Claxton, Jenks, and Taylor, who are employees of York Health Economics Consortium. Study concept and design were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 33 publications
(39 reference statements)
2
46
0
Order By: Relevance
“…While the second BIM was not directly comparable to the one presented here given differences in structure and purpose, the results are still relevant and insightful. In 2018, Claxton et al [87] (an update of Claxton et al [88]) investigated the economic impact of treatment cycling with DMARDs versus using a JAK inhibitor (tofacitinib) directly following methotrexate, or after methotrexate and one or two previous TNFis. The authors report that tofacitinib directly following methotrexate was associated with the lowest total 2-year costs, PMPM costs, and costs per ACR20/50 responder versus adalimumab and etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…While the second BIM was not directly comparable to the one presented here given differences in structure and purpose, the results are still relevant and insightful. In 2018, Claxton et al [87] (an update of Claxton et al [88]) investigated the economic impact of treatment cycling with DMARDs versus using a JAK inhibitor (tofacitinib) directly following methotrexate, or after methotrexate and one or two previous TNFis. The authors report that tofacitinib directly following methotrexate was associated with the lowest total 2-year costs, PMPM costs, and costs per ACR20/50 responder versus adalimumab and etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…The Institute for Clinical and Economic Review reported that TCZ IV monotherapy was less costly and more effective than ADA [14]. In addition, a US-based assessment of annual treatment-related (drug plus administration) costs estimated that the cost per ACR20 responder with SC ADA was numerically higher than the cost per responder with SC TCZ when both biologics were administered as monotherapy ($86,096 vs $62,690) [16]. Despite varied methodologies and patient populations and differences in TCZ use, these studies largely support our results and suggest that IV or SC TCZ monotherapy is a more cost-effective treatment than ADA monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The model assesses the safety profile of tofacitinib in comparison to bDMARDs. Given the heterogeneity of their SAEs reported, we opted to model them all together, considering the onset of severe infections (SI) as being representative of the most common SAEs in RA patients, and applying the frequencies published [35], in line with the approaches previously done [11,34].…”
Section: Adverse Eventsmentioning
confidence: 99%